TRAJECTORY MODEL FOR IDENTIFICATION OF OIL SPILL AROUND THE COAST OF PARI ISLAND, SERIBU ISLANDS, NORTH JAKARTA - Mutiara R. Putri; Agus Setiawan; Titi Sari; B. Mayer; T. Pohlmann (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Oil spills at sea are common in the shipping lanes of the ship as well as the locations of offshore oil drilling. Unfortunately, in every occurrence of the oil spill, we only see the effects after the occurrence, without knowing the original source. Indonesian Numerical Coastal Environmental Assessment (IndoNACE) is research collaboration between Indonesian and Germany by applying satellite data, numerical modeling, and field observations to make an assessment on environmental consequences to oil spills at sea. One of the locations of these research activities is Pari Island, Seribu Islands, North Jakarta. Simulation of hydrodynamic models around Pulau Pari with Hamburg Shelf Ocean Model (HAMSOM) was performed using tides, surface winds, and density difference of seawater as input. Afterwards, by utilizing results of the hydrodynamic model, the spreading of oil spills as well as the origin of the oil spills were estimated using forward and backward trajectory models, respectively. In the case study of Pari Island, there is a presence of thin film of oil in 5 November 2015 that disappears after one day. We suggest that the origin of oil spills were found on the beach Pari Island is expected from the east - northeast of Thousand Islands and is likely from the subsea pipeline which runs from the north to the city of Jakarta or shipping lanes through the Indonesian archipelagic sea lanes (ALKI) I of Karimata Strait up to Java Sea and the Jakarta Bay.